Clinical and audiological study of chronic suppurative otitis media tubotympanic type - G., Priyadarshini; Murali, Sowmiya; James, Febin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Chronic suppurative otitis media (CSOM), tubotymapanic type, despite a commonly encountered disease in otorhinolaryngology has many controversies involved. This study was aimed at bringing few of these aspects to limelight. Methods: The study was conducted in Otorhinolaryngology department, Aarupadai Veedu Medical College and Hospital, Pondicherry, India between September 2015 - August 2016. Total of 207 ears of 180 patients with CSOM tubotympanic type were included. Selected patients were subjected to ENT examination and pure tone audiometry after obtaining history. Results: In this study 35.9% patients belonged to 4th decade and 29.4% to 3rd decade. Among patients with discharge for more than 30 years, 68.8% had moderately-severe hearing impairment and those with discharge for less than 10 years, 60.2% had mild hearing loss. Among patients with large central perforation, 51.4% had moderately-severe hearing loss and those with small central perforation, 68.4% had mild hearing loss. Hearing loss was nearly same in anterior and posterior perforations. On chi square test p value was 0.0874 i.e. >0.05, difference insignificant. Conclusions: In our study most patients were in 4th decade, incidence is equal in both genders. Hearing loss is directly proportional to disease duration and perforation size. Site of perforation does not influence hearing loss.